Sputum smear conversion and treatment outcomes among drug-resistant pulmonary tuberculosis patients in eastern Ethiopia: A 9-years data analysis - Gamachu, Mulugeta; Deressa, Alemayehu; Birhanu, Abdi; Ayana, Galana Mamo; Raru, Temam Beshir; Negash, Belay; Merga, Bedasa Taye; Alemu, Addisu; Ahmed, Fila; Mohammed, Ahmed; Abdulahi, Ibsa M.; Regassa, Lemma Demissei (Frontiers in Medicine, 2022)
Abstract Background: Drug-resistant tuberculosis has become a public health problem throughout the world and about one-third of deaths were attributed to DR-TB from antimicrobial resistance, which accounts for 10% of all TB deaths. However, the scanty evidence on DR-TB contributing factors could affect the level of this deadly case tackling program. Therefore, this study aimed to assess the factors affecting sputum conversion and treatment outcomes among patients with DR-TB in health facilities in Eastern Ethiopia from October 10 to November 10, 2021. A cross-section study design was employed from October 10 to November 10, 2021, in the health facilities providing DR-TB services in Harari Region and Dire Dawa city administration. The medical records of 273 DR-TB patients, were reviewed using structured checklists. Data were entered into Epidata 3.1 version and exported to STATA 14 version for analysis. A multivariable logistic regression model was used to assess the association of independent variables with the first-month sputum smear conversion, while a conditional logistic regression model was used to assess the association of treatment outcome with explanatory variables. The associations were reported using adjusted odds ratios (AOR) at a 95% confidence interval. Results: A total of 273 DR-TB patients were included in this study. The DR-TB treatment outcome was significantly associated with the history of chewing khat (AOR) = 4.38, 95 % CI= 1.62, 11.84), having bilateral lung cavity on baseline chest X-ray (AOR=12.08, 95% CI=1.80, 2.57), having greater than 2+ smear result at baseline (AOR=3.79, 95% CI=1.35, 10.59), and poor adherence (AOR=2.9, 95 CI=1.28, 6.82). The sputum conversion at first month was significantly associated with being HIV-negative (AOR=0.37, 0.17, .82), normal chest X-ray result (AOR=3.77, 1.11, 12.77), having low baseline BMI (AOR= 0.54, .29, .97), and having 2+ sputum smear result (AOR=0.09, 0.012, 0.67). Conclusion: The overall initial sputum smear conversion and the treatment success rate among DR-TB patients were 52.75% and 66.30% respectively. So, strengthening and implementing nutrition assessment, and patient counseling during DOTs service and drug compliance could result in early sputum conversion and better treatment outcomes. Keywords: Smear, Sputum, Ethiopia, Tuberculosis, Pulmonary, Treatment Outcome